558 Use Of Balloon-Guide Catheters For Concomitant Mechanical Thrombectomy And Carotid Revascularization With Flow-Arrest Results In Significantly Lower sICH And Better 90-Day Outcomes In Tandem Stroke Patients: A Propensity Score-Matched Study. (April 2023) - Baig, Ammad; Waqas, Muhammad; Cappuzzo, Justin Mark; Kuo, Cathleen; Donnelly, Brianna; Monteiro, Andre; Davies, Jason; Siddiqui, Adnan Hussain; Levy, Elad I.
Abstract : INTRODUCTION: A larger than normal clot burden accounts for worse presentation and poorer thrombectomy outcomes in tandem stroke cases. METHODS: A prospectively maintained database was retrospectively searched for patients who presented with a tandem stroke. Patients were dichotomized into two groups; those treated with BGCs and those treated without BGCs. A one-to-one matched propensity score analysis was performed to adjust for treatment selection bias using the nearest-neighbor matching technique for covariates (baseline comorbidities and stroke severity). Patient demographics, presentation characteristics, and procedural details were recorded. Outcomes were assessed as periprocedural sICH, in-hospital mortality, and 90-day mRS. Mann-whitney U test, and multivariate logistic regression was performed to compare the procedural parameters and the clinical outcomes between groups. RESULTS: We included 125 patients (BGC: 85 [40 after PSM]; No BGC: 40 [40 after PSM]). Concomitant carotid revascularization (stenting or angioplasty) was performed in all cases. After PSM, no difference was seen between the two groups in terms of comorbidities, and initial stroke severity. BGC group had significantly lower procedure duration (61.5% vs. 77.9% (OR = 0.996; P = 0.006)), lower NIHSS at discharge (8.0% vs. 11.0% (OR = 0.987; P = 0.042)), and higher odds of good outcomes (mRS 0-2 at 90-day) (52.3% vs. 27.5% (OR = 0.34; P = 0.040)). On multivariate regression analysis, BGC group had significantly higher rate of first-pass effect (mTICI 2B-3) (OR = 0.660, 95% CI = 0.480-0.908;P = 0.013), and a lower periprocedural sICH rate (OR = 0.615, 95% CI = 0.406-0.932; P = 0.025). No difference in in-hospital mortality was observed (OR = 1.591; 95% CI = 0.976-2.593; P = 0.067). CONCLUSIONS: Use of BGCs for concomitant mechanical thrombectomy and carotid revascularization with flow-arrest is safe and results in superior clinical and angiographic outcomes in tandem stroke patients.